2014
DOI: 10.1155/2014/890316
|View full text |Cite
|
Sign up to set email alerts
|

Flow Boiling Heat Transfer Enhancement by Using ZnO-Water Nanofluids

Abstract: Nanofluids are liquid suspensions containing nanoparticles that are smaller than 100 nm. There is an increased interest in nanofluids as thermal conductivity of nanofluids is significantly higher than that of the base liquids. ZnO-water nanofluids with volume concentration of ZnO particles varying from 0.0001 to 0.1% were prepared using ultrasonic vibration mixer. Thermal conductivity of the ZnO-water fluids was investigated for different sonication time using thermal property analyzer (KD2 Pro). Thermal condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Om Shankar et al [22] studied an experiment on the flow boiling HTC by using ZnO-water nanofluids. Their 780 mm long annular test section was consisted with an electrically heated rod and a 21.8 mm internal diameter outer borosilicate glass tube.…”
Section: Nanofluids Enhancement On Boilingmentioning
confidence: 99%
“…Om Shankar et al [22] studied an experiment on the flow boiling HTC by using ZnO-water nanofluids. Their 780 mm long annular test section was consisted with an electrically heated rod and a 21.8 mm internal diameter outer borosilicate glass tube.…”
Section: Nanofluids Enhancement On Boilingmentioning
confidence: 99%
“…Similar studies were reported in the open literature. In this context, Prajapati OS and Rohatgi N 32 conducted experiments in annular test section by using ZnO/water nanofluids for different concentrations. From their results they concluded that heat transfer increases with heat flux, mass flux and concentrations of the nanofluid.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the available literature, a group of researchers concluded that nanofluids deteriorate the heat transfer. 13,14,26,34 But many other researchers 20,21,2933 have reported that nanofluids enhance the heat transfer. The common reason mentioned for enhancement and deterioration was the same, i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The addition of nanoparticles can result in the reduction of an overall heat transfer coefficient for the selected plate heat exchanger [21]. Flow boiling heat transfer with various nanofluids is discussed in [22][23][24][25], where [23,25], focus on convective flow flow boiling heat transfer in minichannels, and [24] on the experimental investigation of heat transfer characteristics of the developed laminar flow.…”
Section: Introductionmentioning
confidence: 99%